1985
DOI: 10.2337/diab.34.7.710
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Responses to Growth-Hormone-Releasing Hormone and Thyrotropin-Releasing Hormone in Diabetic Patients With and Without Retinopathy

Abstract: Growth hormone (GH) responses to growth-hormone-releasing hormone (GRH) and thyrotropin-releasing hormone (TRH) were studied in 17 diabetic patients. Ten patients (group 1) had retinopathy corresponding to stage III-V (Scott's classification), and the remaining seven patients (group 2) had no retinopathy despite longer duration of diabetes in comparison with the patients in group 1. There were no differences in age, percent of ideal body weight, and serum HbA1 levels between the two groups. Basal serum GH leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The contribution of the GH/IGF-I axis to the pathophysiology of diabetic retinopathy (180,612) was described nearly four decades ago based on the elevated circulating GH levels found in diabetic subjects (275,445,497), the halted progression of diabetic retinopathy after anterior pituitary ablation (335) or radiation (496), and the reduced incidence of the disease in GH-deficient diabetic patients (14). Moreover, evidence that IGF-I reverses protection by a GH antagonist against ischemiainduced retinopathy (510), promotes VEGF-mediated retinal angiogenesis (443,511), and induces most of the alterations seen in diabetic retinopathy (475) substantiates the causative role of the GH/IGF-I axis in the development of the disease.…”
Section: B Diabetic Retinopathymentioning
confidence: 99%
“…The contribution of the GH/IGF-I axis to the pathophysiology of diabetic retinopathy (180,612) was described nearly four decades ago based on the elevated circulating GH levels found in diabetic subjects (275,445,497), the halted progression of diabetic retinopathy after anterior pituitary ablation (335) or radiation (496), and the reduced incidence of the disease in GH-deficient diabetic patients (14). Moreover, evidence that IGF-I reverses protection by a GH antagonist against ischemiainduced retinopathy (510), promotes VEGF-mediated retinal angiogenesis (443,511), and induces most of the alterations seen in diabetic retinopathy (475) substantiates the causative role of the GH/IGF-I axis in the development of the disease.…”
Section: B Diabetic Retinopathymentioning
confidence: 99%
“…Thus, Richards et al (1984) andPress et al (1984 in poorly controlled Type 1 diabetic subjects found a GH response to GHRH which was normal in absolute terms, but was considered to be "inappropriate" for the prevailing plasma glucose levels. On the other hand, Sharp et al (1984b) recorded in fasting hyperglycemic insulin-dependent patients with retinopathy a GH response which tended to be reduced, whereas Kaneko et al (1985) observed in normoglycemic retinopathic diabetic subjects a GH response to GHRH significantly higher than in normal subjects. GH hyperresponsiveness to GHRH has also been reported in streptozotocindiabetic rats (Locatelli, Miyoshi, Bestetti, Rossi and Miiller 1985).…”
Section: Discussionmentioning
confidence: 62%
“…GHRH, was characterized, studies on pituitary sensitivity to GHRH have been performed in both normal (Sharp et al 1984a;Masuda et al 1985) and diabetic subjects (Press et al 1984;Richards et al 1984;Sharp et al 1984b;Kaneko et al 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies revealed only a weak or rather no association between IGF-I and diabetic retinopathy. For example no relationship was found between diabetic retinopathy and plasma IGF-I levels [65], serum IGF-I levels [66][67][68][69][70][71] or vitreous free IGF-I levels (in this case after adjusting for total intravitreous protein concentration) [72]. Nevertheless, in states of elevated IGF-I levels such as pregnancy and puberty, a progression of retinopathy was demonstrated [73][74][75].…”
Section: Alteration Of Growth Factor Expressionmentioning
confidence: 94%